Therapeutic advances in hepatocellular carcinoma: an update from the 2024 ASCO annual meeting - Yang, Hongyuan; Liu, Yanju; Zhang, Na; Tao, Fengbao; Yin, Gaozheng (Frontiers in Oncology, 2024)
Hepatocellular carcinoma (HCC) remains a leading cause of cancer-related deaths worldwide. Recent advances in immunotherapies, targeted therapies, and combination treatments have significantly improved outcomes for many patients with HCC. This review summarizes key findings from the 2024 ASCO Annual Meeting, focusing on emerging therapies, including immune checkpoint inhibitors (ICIs), CAR-T cell therapies, oncolytic viruses, and locoregional treatments like transarterial chemoembolization (TACE) and hepatic arterial infusion chemotherapy (HAIC). ICIs, particularly when combined with other agents, have shown promising efficacy, though challenges such as immune-related adverse events and resistance mechanisms remain. CAR-T cell therapies and oncolytic viruses offer novel therapeutic avenues for advanced HCC, but their long-term efficacy in solid tumors is still under investigation. Locoregional therapies, especially in combination with systemic treatments, continue to play a critical role in managing unresectable HCC and improving conversion rates to surgical resection. Additionally, the potential of biomarkers, such as hypoxia scores and CTNNB1 mutations, is being explored to better personalize treatment and predict patient responses. These biomarkers could pave the way for more targeted and effective therapeutic strategies. Overall, the recent studies presented at the ASCO meeting highlight progress in HCC treatment, underscoring the importance of continued innovation. Future research should focus on overcoming resistance mechanisms, optimizing combination therapies, and integrating biomarker-driven approaches to improve patient outcomes and enhance personalized treatment strategies.